2011
DOI: 10.1051/limn/2011008
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic vegetation as an indicator of littoral habitats and various stages of lake aging in north-eastern Poland

Abstract: -The habitats of 356 phytocoenoses dominated by 15 species of aquatic plants were investigated. Among the properties of water, Na + , pH, total Fe, Ca 2+ , NO 3 x , SO 4 2x , hardness and COD-KMnO 4 were the most important in differentiating the habitats of the phytocoenoses studied. Considerable physicochemical differences were found between the waters of the phytocoenoses of Ranunculus circinatus (hard waters rich in Na + ), Nuphar pumila (soft waters with high levels of total Fe), Elodea canadensis, Ceratop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…3). The presence of Ceratophyllum demersum shows that the basin was influenced by limeenriched water (Kłosowski et al 2011). The mentioned taxa suggest that the water depth could have been approximately 3 m (Hannon, Gaillard 1997).…”
Section: Development Of Flora and Water Basinmentioning
confidence: 95%
“…3). The presence of Ceratophyllum demersum shows that the basin was influenced by limeenriched water (Kłosowski et al 2011). The mentioned taxa suggest that the water depth could have been approximately 3 m (Hannon, Gaillard 1997).…”
Section: Development Of Flora and Water Basinmentioning
confidence: 95%
“…in northeastern Europe (Heikkilä and Seppä 2003;Seppä and Poska 2004). The presence of Ceratophyllum demersum shows that Linówek was influenced by lime-rich water (Kłosowski et al 2011). At *4500 B.C., submerged plants almost completely disappeared from the lake, an event that occurred at the time of an increased share of Botryococcus and Pediastrum boryanum (Fig.…”
Section: Postglacial History Of Vegetationmentioning
confidence: 99%
“…In studies conducted in Lake Sakadaš (Croatia), it was demonstrated that the composition of invertebrates associated with macrophytes (M. spicatum L.) is consistent with the trophy of the studied lake [35]. Some elodeids, for example M. spicatum L., typically occur on mineral surfaces of meso to eutrophic lakes [36].…”
Section: Reservoirsmentioning
confidence: 80%